7Ps of service marketing mix in business - for a service business / Nordayana Zulkifli - Zulkifli, Nordayana (UiTM Cawangan Negeri Sembilan, 2022)
The success formula for each business marketing plan is to deliver a unique plan and experience that is different from their competitors, which will satisfy their target buyers. Derive from the marketing concept, the marketing mix evolves. The marketing mix is allocating the right product, at the right place, right time, and definitely at the right price. The businesses need to undergo proper planning regarding all these and they must know their business really well. The marketing mix starts with 4P's such as product, price, place, and promotion. Meanwhile, the 7 P's of the service marketing mix is the expansion of the 4 P's which include people, process, and physical evidence. Service marketing mix always been used by business that offers services.